An integration of antecedents and outcomes of business model innovation: A meta-analytic review - Zhang, Hongfang; Xiao, Huilin; Wang, Yanling; Shareef, Mahmud A.; Akram, Muhammad Shakaib; Goraya, M. Awais Shakir (Journal of business research, 2021)
Despite the existence of a large body of literature on the business model innovation (BMI), comprehensive empirical reviews of the antecedents and outcomes of BMI are limited. This study develops a theoretical framework and carries out a meta-analysis of empirical studies to investigate the relationships among BMI, its antecedents, and firm performance. The results validate a significant positive association between external and internal antecedents and BMI. Likewise, BMI is positively associated with firm performance. Besides, BMI and firm performance measurement reveal borderline significant moderating effects on the relationship between BMI and firm performance, and environmental uncertainty has a significant positive effect on the BMI-firm performance link. However, the moderating effect of BMI measurement on the antecedents-BMI relationship is not confirmed during the subgroup analyses. This study contributes to research on BMI and assists practitioners in interpreting and developing BMI strategies for organizations.